Transcendent Interview: an Alternative Method of Writing the History of Islam In The Archipelago Based on Irfani Epistemology - Faidi, Ahmad; Shofiyuddin, M; Sidiq, Uthman Okanlawon (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2025)
The debate on the use of knowledge sources in writing Islamic history is widely debated by scholars, both Muslims and non-Muslims. However, there is a stigmatized aspect that is forgotten to be used as a source of historical purification, namely the irfani area. This article aims to examine irfani epistemology as a methodological basis in writing Islamic history. The focus of this study is to examine the limitations of the positivistic-empirical method in reconstructing objective Islamic history, the position of manuscripts, chronicles, and oral traditions in the classification of primary historical sources, and transcendental interviews as an alternative source criticism method. The method used in this study is library research with a qualitative approach. This study reveals how the irfani approach can be an alternative method in writing Islamic history in the archipelago. This article contributes to strengthening comprehensive methods and approaches to writing Islamic history. Transcendental interviews can be used as an alternative source criticism method to verify the originality and validity of information in manuscripts, chronicles, and oral traditions. This article contributes to the development of sources of Islamic history writing with irfani approaches and methods that are in direct contact with authoritative societies